The timeliness of George Herbert Mead - Joas, Hans; Huebner, Daniel R. (The University of Chicago Press, 2016)
Introduction / Hans Joas and Daniel R. Huebner -- History, historiography, historical sociology -- Changing "movements of thought in the nineteenth century": historical text and historical context / Charles Camic -- On Mead's long lost history of science / Daniel R. Huebner -- Pragmatism and historicism: Mead's philosophy of temporality and the logic of historiography / Hans Joas -- George Herbert Mead and the promise of pragmatist democracy / Robert Westbrook -- The theory of intersubjectivity as a theory of the human being: George Herbert Mead and the German tradition of philosophical anthropology / Karl-Siegbert Rehberg -- Nature, environment, process -- Naturalism and despair: George Herbert Mead and evolution in the 1880s / Trevor Pearce -- George Herbert Mead as a socio-environmental thinker / Bradley H. Brewster and Antony J. Puddephatt -- Social worlds: the legacy of Mead's social ecology in Chicago sociology / Daniel Cefaï -- Mead, Whitehead, and the sociality of nature / Michael L. Thomas -- Cognition, conscience, language -- Mead, the theory of mind, and the problem of others / Ryan McVeigh -- Imitation and taking the attitude of the other / Kelvin Jay Booth -- Mead meets Tomasello: pragmatism, the cognitive sciences, and the origins of human communication and sociality / Frithjof Nungesser -- Conscience as ecological participation and the maintenance of moral perplexity / Joshua Daniel -- Presentation and re-presentation: language, content, and the reconstruction of experience / Roman Madzia -- G. H. Mead's understanding of the nature of speech in the light of contemporary research / Timothy Gallagher